A Analysis of the Effect of Profitability and Liquidity Levels as a Response to the Capital Structure at PT Telkom Indonesia (Persero) Tbk in 2016-2023 - Sombolayuk, Nadia; Taliding, Arianto; Guntur, Ihsan (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
This research aims to analyze the influence of profitability and liquidity on the capital structure of PT Telkom Indonesia (Persero), Tbk in 2016-2023. Using quantitative methods with secondary data in the form of company financial reports, the independent variables in this research are profitability and liquidity while the dependent variable is capital structure. Data were analyzed using multiple linear regression with the help of SPSS 22, as well as classical assumption tests to ensure the validity of the model. Based on the regression analysis of the t test results in the coefficients table, profitability as measured using ROA and ROE has a significant value smaller than 0.05, which means it has significant effect on capital structure. Liquidity measured using CR dan QR has a significant value greater than 0.05, which means it has no significant effect on capital structure. Then the F test results in the Anova table have an F-count > F-table value and a significant value smaller than 0.05, thus indicating that profitability and liquidity influence capital structure simultaneously